Paracetamol-Induced Liver Damage and Effect of Prosopis africana Seeds Extract on Liver Marker Enzymes of Wistar Albino Rats: Effect of Prosopis africana Seed Extract on Liver - Parker, Joshua; Chizoba, Anosike Joy; Okpashi, Victor Eshu; Okwesili Fred, Chilentugo Nwodo (Biological Sciences - PJSIR, 2019)
This study was carried to determine the effect of Prosopis africana seed extract after induction of paracetamol in Wistar albino rats to ascertain its ameliorating capacities in terms of liver damage. The assay was done on alkaline phosphatase, alanine aminotransferase, aspartate aminotransferase, and hematological parameters. Thirty-two Wistar albino rats with an average weight of 120-180 g were used for this investigation. The P. africana seeds were extracted by maceration after 24 h fermentation in chloroform-methanol ratio 2:1. The animals were administered 2500 mg/kg of paracetamol upon 24 h starvation to induce liver damage. After administering 5000 mg/kg body weight (BW), the extract showed no acute toxicity. Serum alanine phosphatase, alanine aminotransferase, and aspartate aminotransferase levels decreased in all the test groups as compared to paracetamol group. The results depicted that P. africana seeds extract are effective in the regeneration of the damaged liver cells by averting enzyme leakage into the bloodstream.